Substantiation of the ratio of biofuel and kerosin in the mixture for its application as aviation fuel - V. M. Samoylenko; K. I. Gryadunov; A. N. Timoshenko; S. Ardeshiri (Научный вестник МГТУ ГА, 2020)
Today, technologies for the production of alternative fuels and for the development of engines on different operating principles are actively developing, due to both the tightening of the environmental requirements of ICAO (International Civil Aviation Organization) for harmful emissions into the atmosphere and the depletion of non-renewable resources, and the interests of the oil importing countries. Strict requirements are imposed on the quality of aviation fuels related to ensuring the reliability of aviation technology and flight safety. Requirement toughening for quality indicators will inevitably lead to higher fuel prices, so today we can observe some concessions in domestic and foreign regulatory documents to certain quality indicators of aviation fuels, for example, to indicators of low-temperature properties. It follows that the use of petroleum fuels will sooner or later become inappropriate. Technologies to produce synthetic and biological fuels from various types of raw materials make it possible to obtain fuel with close quality indicators to traditional kerosene, but it has not yet been completely replaced. Therefore, today we are considering the use of alternative fuels in a mixture with petroleum kerosene in various proportions. The question remains open: in what proportion is it possible to use mixtures of alternative fuel with kerosene on the aircraft without any negative consequences for their operation. Based on the known dependencies, a mathematical model is proposed for calculating some operational indicators of fuel, engine and aircraft depending on the proportion of mixing alternative fuel and kerosene. In accordance with the calculations, the most rational ratio of petroleum kerosene and SPK fuel is substantiated both from the point of view of the necessary operational properties and from the point of view of economic feasibility.